Analisis Kinerja Keuangan Berdasarkan Analisis Rasio pada PT. Jakarta International Hotels & Development Tbk (JIHD) - Victoriano Hidayat; Harsana, Livia Christy; Adelly Gabriella; Dyah Cahayasari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Financial statement analysis based on ratio analysis at PT JIHD has many benefits in assessing the risk and economic health of this company. PT JIHD's financial ratios consisting of liquidity, solvency, activity, and profitability ratios are analyzed using financial ratio calculation techniques. The research method used is descriptive quantitative or studying a phenomenon based on numbers. The data used is secondary data in the form of data series obtained from library sources, a quantitative descriptive approach is used in the preparation of this publication. The financial statements of PT JIHD for the period 2020-2023 became the research sample. Based on the results of the study, the financial ratios of PT JIHD in the period 2020 - 2023 showed a poor condition because they were below the industry ratio, but showed growth in a more positive direction. The unfavorable ratio condition is a result of the co-19 pandemic that has hit the world, especially Indonesia. This means that JIHD was able to manage its capital and assets during the pandemic, so that it could survive and slowly recover from these conditions. This also shows JIHD's strong commitment and the implementation of several good policies.